2013
DOI: 10.1039/c3cc00036b
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic tuning of ligand donor properties in (Ttz)CuCO through remote binding of H+ (Ttz = hydrotris(triazolyl)borate)

Abstract: Complexes with bulky hydrotris(triazolyl)borate (Ttz) ligands, TtzCuCO, were used to probe how acids change the donor properties of Ttz ligands. (Ttz(tBu,Me))CuCO shows four distinct protonation states and a gradual increase in the CO stretch. The increased electrophilic nature of the Cu center upon protonation leads to enhanced C-H activation catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…[26][27][28] In contrast to altering the electronic properties by synthetic changes, our group has demonstrated that the electron donating properties of Ttz ligand can be tuned by protonation at the fourth position nitrogen atom of the triazole ring (Figure 2, right). [29] This point is described further below. Bulky tris(3,5-R,R'-1, 2, 4-triazolyl)borate (Ttz R,R' ) ligands support low coordinate metalcenters that are suitable for catalysis.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…[26][27][28] In contrast to altering the electronic properties by synthetic changes, our group has demonstrated that the electron donating properties of Ttz ligand can be tuned by protonation at the fourth position nitrogen atom of the triazole ring (Figure 2, right). [29] This point is described further below. Bulky tris(3,5-R,R'-1, 2, 4-triazolyl)borate (Ttz R,R' ) ligands support low coordinate metalcenters that are suitable for catalysis.…”
Section: Introductionmentioning
confidence: 97%
“…Bulky tris(3,5-R,R'-1, 2, 4-triazolyl)borate (Ttz R,R' ) ligands support low coordinate metalcenters that are suitable for catalysis. [8,[29][30][31][32][33][34][35][36][37] Ttz complexes of copper(I) show that electrophilic C-H activation reactions can be enhanced by ligand protonation. [29] Ttz ligands offer facial coordination and ease of steric modification at the metal center similar to the more commonly used tris(3-R-5-R'-1,2-pyrazolyl)hydroborate (Tp R,R' ) ligands ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly(triazolyl)borates [19,[62][63][64][65][66][67][68][69][70] are an attractive class of scorpionate ligands due to two important features: first, they are more electron-withdrawing than their poly(pyrazolyl)borate counterparts [71] and second, the remote exo-ring-nitrogen atoms, in the fourth position on the triazole rings, represent an additional binding site for metal ions resulting in new structures. In particular, they may bridge between metal centers and create a coordination polymer or may take part in hydrogen-bond interactions, assisting the formation of two-dimensional water intercalate or water-layer clathrates [72], thus leading to water soluble species [66,73,74].…”
Section: Introductionmentioning
confidence: 99%
“…We have had a long-standing interest in creating scaffolds that place hydrogen bonds near and far from the metal center. [17][18][19][20][21][22][23][24] The work herein describes the synthesis of a novel tripodal, monoanionic ligand based upon amino substituted pyrazole rings (LH) that offers hydrogen bonds near the metal center. In the course of our synthetic efforts towards novel tripodal ligands, we discovered that 3-(NH-t-Butyl)-5-methyl-pyrazole (LH) can support metal complexes ((LH) n MX 2 ) which contain a network of six to eight intramolecular hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%